Analisis laporan keuangan untuk mengukur kinerja keuangan perusahaan pada PT Akbar Indo Makmur Stimec Tbk periode 2020-2021 - Lidia Pratiwi; Wilisa Wilisa; Nurul Asyifa Qatrunnada; Hasriana Hasriana; Hariany Idris (Bata Ilyas Journal of Accounting, 2023)
Evaluating the financial performance of a company is important. This allows companies to measure and evaluate them so that they have a complete picture of the company's financial position. Financial statement analysis methods can be used to measure the financial performance of a company. The method of financial analysis includes several financial ratios such as liquidity, solvency, activity and profitability ratios. This study aims to determine the financial performance of PT Akbar Indo Makmur Stimec Tbk for the 2020-2021 period. Using the ratio of liquidity, solvency, activity and profitability. According to the results of this study, PT Akbar Indo Makmur Stimec Tbk is represented by a rate that fluctuates every year due to an increase or decrease in items in the financial statements such as sales, inventory, and profit.